(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Ayurveda is not only an ancient medical science but it is a science which gives understanding about life. The scope of Ayurveda is to maintain the health of a healthy person and to cure those suffering from diseases. Since last few decades due to drastic change in lifestyle, dietary habits and working pattern overall human population is facing increased burden of several diseases. Late night sleeping habits, increased fast food consumption, overeating and increased sugar intake are major changes observed in current era. Lifestyle disorder is a broad term given to all diseases which arises because of unhealthy lifestyle. Diabetes is the most common lifestyle disease affecting population worldwide at large. Now a day various researches carried out at different institutions found that variety of Ayurvedic drugs and therapies are successful in controlling diabetes, improving lifestyle of patient and thereby preventing further complications. The present review article is aimed at compiling data on promising Ayurvedic remedies that have been evaluated for their efficacy as an anti-diabetic remedy at various national and international institutions. This review article gives an idea about the efficiency of various anti-diabetic Ayurvedic treatment modalities in present era public.